High-resolution magnetization transfer MRI in patients with cervical spondylotic myelopathy. (May 2018) - Suleiman, Linda I.; Weber, Kenneth A.; Rosenthal, Brett D.; Bhatt, Surabhi A.; Savage, Jason W.; Hsu, Wellington K.; Patel, Alpesh A.; Parrish, Todd B.
Highlights: Magnetization transfer contrast has been established as a marker of myelin integrity. MT MRI may have the potential to better detect structural changes in white matter than conventional T1 and T2 imaging techniques. The lowest intervertebral MTR negatively correlated with the Nurick score among CSM patients. Abstract: Magnetization transfer (MT) contrast has been established as a marker of myelin integrity, and cervical spondylotic myelopathy is known to cause demyelination. Ten patients with clinical and magnetic resonance imaging (MRI) manifestations of cervical spondylotic myelopathy (CSM) were compared to the MRIs of seven historic healthy controls, using the magnetization transfer ratio (MTR) and Nurick scores as the primary metrics. Transverse slices through the intervertebral discs of the cervical spine were acquired using a gradient echo sequence (MEDIC) with and without an MT saturation pulse on a 3 Tesla Siemens Prisma scanner (TR = 300 ms, TEeff  = 17 ms, flip angle = 30°, in-plane resolution = 0.47 × 0.47 mm 2 ). The CSM patients tended to have a lower mean MTR (30.4 ± 6.5) than the controls (34.8 ± 3.8), but the difference was not significant (independent samples t -test, p = 0.110, Cohen's d  = 0.80). The mean MTR across all intervertebral disc levels was not significantly correlated to the Nurick score (Spearman's ρ = −0.489, p = 0.151). The intervertebral level with the lowest MTR in each cohort was not significantly different between groups (equal variances not assumed, t = 1.965, dof = 14.8, p = 0.068, Cohen's d  = 0.88), but the CSM patients tended to have a lower MTR. The mean MTR at this level was negatively correlated to the Nurick score among CSM patients (Spearman's ρ = −0.725, p = 0.018). CSM patients tended to have decreased MTR indicating myelin degradation compared to our healthy subjects, and MTR was negatively correlated with the severity of CSM.